Optical Properties & Structural of Dioxide Thin Films Prepared by Chemical Spray Pyrolysis - latif, D. M. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
X-ray diffraction pattern reveled the tetragonal crystal system of SnO2  Thin films of SnO2 were prepared on glass substrates using Spray Pyrolysis Technique. The absorption and transmition spectra were recorded in the rang of 300-900nm,  the   spectral   dependences   of   absorption coefficient were calculated   from   transmission spectra. The direct and allowed optical  energy gap has been evaluated from plots of   (Î±hÏ…)Â²  vs. (hÏ…) . The energy gap was found to be  2.4-2.6eV.  The optical constant such as extinction coefficient( k )  and absorption coefficient ( Î±) have been evaluated.